Analisis Faktor-faktor Motivasi Dan Kedisiplinan Pegawai PT Mahkota Group Tbk - Medan Medan - Manda Dwipayani Bhastary (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
This study aims to determine the dominant factors that determine the work motivation of employees of PT Mahkota Group Tbk - Medan  and to determine the dominant factors that determine the discipline of employees of PT Mahkota Group Tbk - Medan. The population is the total number of objects of this research, namely all employees in the area of PT Mahkota Group Tbk - Medan  as many as 41 people and at the same time being the sample in this study. Data collection techniques in this study were a list of questions (Questioners) and. The results show that the instrument is valid because the KMO MSA (value exceeds the 0.50 significance limit. Of the 3 factors for motivational variables analyzed and after passing the KMO MSA analysis, it turned out that from the results of computer extraction analysis it became 1 factor. Factor 1 was able to explain 80.426% of the variation, while from the 3 factors for the analyzed discipline variables and after passing the KMO MSA analysis, it turned out that the results of the computer extraction analysis became 1 factor.